The name of the wild man: colonial arbiru in East Timor - Roque, Ricardo (2020)
In this chapter I explore the indigenous incorporation and critique of colonial outsiders through nicknaming. I draw on the history of colonial warfare in Timor-Leste, a former Portuguese colony, in the nineteenth and twentieth centuries, to consider naming practices as a way through which the mimetic excesses of colonial agents could be simultaneously acknowledged, feared, criticized, and even cursed as a form of savagery. For this purpose I follow the cross-cultural history of the term arbiru. East Timorese people used this term as a nickname for a Portuguese colonial officer in the 1890s. Portuguese colonial accounts understood this usage as Timorese recognition of European supremacy and supernatural powers. Nevertheless, the colonial viewpoint failed to capture the veiled negative meanings that the Timorese name conveyed. In contrast, this chapter argues, the term arbiru entailed hidden indigenous criticism and cursing of the colonizers’ excessive, threatening, and transgressive actions. It was a linguistic gesture for naming the wild and wicked nature of colonial mimesis.